Den litterære diskurs - Hansen, Per Krogh (K&K - Kultur og Klasse, 2005)
Jørgen Dines Johansen: Literary Discourse. A Semiotic-Pragmatic Approach to Literature, Toronto 2002 (University of Toronto Press).